OP0101 Exploring pain and the impact of jia on adolescents and young adults: a mixed-methods study. (12th June 2018) - Chaplin, H; Ioannou, Y.; Sen, D.; Lempp, H.; Norton, S.
Abstract : Background: Young people with Juvenile Idiopathic Arthritis (JIA) have emphasised concerns about the extent to which factors beyond inflammation affect their daily lives, particularly with persistent pain, despite effective clinical management into adulthood. Pain experience and impact on daily life remains relatively unexplored in the adolescent and young adults (AYAs). Objectives: This study aimed to: a) establish prevalence of current pain in AYAs with JIA, b) determine associations with pain intensity, and c) qualitatively explore perceived impact of JIA on daily life. Methods: This cross-sectional mixed methods study recruited 85 JIA patients attending AYA Rheumatology clinics in London. It assessed pain intensity (APPT) as the primary outcome, with the following predictor variables: mood (HADS), illness perceptions (B-IPQ), fatigue (FACIT–F), functioning (WSAS), quality of life (MSK-HQ), demographics and disease activity. Analysis was conducted using spearman's correlations and hierarchical multiple linear regression. Semi-structured interviews about the impact of JIA with a subset of 15 participants were conducted and analysed via inductive thematic analysis. Ethical/R and D approvals and informed consent were obtained. Results: Participants completing the survey were predominantly female (68.2%), White British (65.9%), aged 16–25 (mean=19.63, SD=2.23), with Polyarticular (40%) the most common subtype, and 10.43 years mean disease duration (SD=5.16). Prevalence of current pain was 91.8%, with 37% reporting medium-to-severe pain. In interviews (66% female, 33% white British, mean age 19.92, mean disease duration 12 years), despite high prevalence, pain was only ranked fourth (6/15) as most impacting on daily life by those interviewed. The other top areas chosen were: fatigue (9/15), mood (8/15), social aspects (8/15), and impairments in functioning (5/15). Pain was reported in terms of impact on personal relationships (e.g. changes to mood linked to pain) and other restrictions preventing life as a 'normal' young person. In the survey, pain intensity was moderately associated with biological variables, e.g. active joints ( rs =0.27), and strongly associated with psychological variables, e.g. depression and illness related distress ( rs =0.53 and rs =0.50). Demographic and clinical variables (Step 1) explained 13.4% of variance in pain intensity. Adding distress, fatigue and functioning (Step 2) explained an additional 24.8%, and illness perceptions (Step 3) explained a further 30.4%. Identity and Consequences illness perceptions accounted for 70.5% of the association between active joints and pain. Conclusions: Findings support an approach of the biopsychosocial model of pain in clinical practice. The impact of JIA occurs during active disease but also persist during remission, going beyond pain and inflammation. These impacts need to be monitored by healthcare Disclosure of Interest: None declared